Small Intestine Bacterial Overgrowth is associated with increased Campylobacter and epithelial injury in duodenal biopsies of Bangladeshi children. - Shah Mohammad Fahim; Jeffrey R Donowitz; Ekaterina Smirnova; Ning-Juin Jan; Subhasish Das; Mustafa Mahfuz; S M Abdul Gaffar; William A Petri; Chelsea Marie; Tahmeed Ahmed (PLoS Neglected Tropical Diseases)
Small intestine bacterial overgrowth (SIBO) has been associated with enteric inflammation, linear growth stunting, and neurodevelopmental delays in children from low-income countries. Little is known about the histologic changes or epithelial adherent microbiota associated with SIBO. We sought to describe these relationships in a cohort of impoverished Bangladeshi children. Undernourished 12-18-month-old children underwent both glucose hydrogen breath testing for SIBO and duodenoscopy with biopsy. Biopsy samples were subject to both histological scoring and 16s rRNA sequencing. 118 children were enrolled with 16s sequencing data available on 53. Of 11 histological features, we found that SIBO was associated with one, enterocyte injury in the second part of the duodenum (R = 0.21, p = 0.02). SIBO was also associated with a significant increase in Campylobacter by 16s rRNA analysis (Log 2-fold change of 4.43; adjusted p = 1.9 x 10-6). These findings support the growing body of literature showing an association between SIBO and enteric inflammation and enterocyte injury and further delineate the subgroup of children with environmental enteric dysfunction who have SIBO. Further, they show a novel association between SIBO and Campylobacter. Mechanistic work is needed to understand the relationship between SIBO, enterocyte injury, and Campylobacter.